Effect of mindfulness training on fatigue and recovery in elite volleyball athletes: A randomized controlled follow-up study - Coimbra D.R. (2021)
© Journal of Sports Science and Medicine.Volleyball is a team sport with high physical and perceptual-cog-nitive demand, hence, increasing the perception of physical and mental fatigue during a competition. To alleviate fatigue (physi-cal and mental), mindfulness and music have been proposed. The aim of this study was to analyze the effect of mindfulness-based mental versus music training on mental fatigue, physical fatigue, and recovery in elite competitive female volleyball athletes using a randomized two-controlled study with follow-up. Participants were 30 elite female Brazilian volleyball athletes. Athletes were randomly assigned to the following groups: 1) mindfulness-based mental training group (MBMT); 2) music-based training group (MBT); or 3) control group (CG). Three variables were evaluated as follows: 1) recovery based on total quality recovery; 2) mental fatigue visual analog scale; and 3) physical fatigue visual analog scale. Regarding recovery, there was no difference between the MBMT, MBT, and CG groups (p > 0.05). A difference in mental fatigue was noted between MBT and CG at follow-up [F(2,26) = 5.71, p = 0.009; large]. Regarding physical fatigue, there was no difference between the MBMT, MBT, and CG groups (p > 0.05). The mindfulness intervention effectively attenuated the mental fatigue caused by competition in volleyball athletes. These results will assist coaches and staff in providing fatigue management and reinforce the applicability of mental training in sports.